Answer:
The one with the higher amount they put away
Step-by-step explanation:
For this, we will be using the quadratic formula, which is
, with a=x^2 coefficient, b=x coefficient, and c = constant. Our equation will look like this: ![x=\frac{-6+/-\sqrt{6^2-4*(-2)*3}}{2*(-2)}](https://tex.z-dn.net/?f=%20x%3D%5Cfrac%7B-6%2B%2F-%5Csqrt%7B6%5E2-4%2A%28-2%29%2A3%7D%7D%7B2%2A%28-2%29%7D%20)
Firstly, solve the multiplications and the exponents: ![x=\frac{-6+/-\sqrt{36+24}}{-4}](https://tex.z-dn.net/?f=%20x%3D%5Cfrac%7B-6%2B%2F-%5Csqrt%7B36%2B24%7D%7D%7B-4%7D%20)
Next, do the addition: ![x=\frac{-6+/-\sqrt{60}}{-4}](https://tex.z-dn.net/?f=%20x%3D%5Cfrac%7B-6%2B%2F-%5Csqrt%7B60%7D%7D%7B-4%7D%20)
Next, your equation will be split into two:
. Solve them separately, and your answer will be
I got 11,304. I don't know if that's right or if it's wrong. Let me check again
Answer:
<em>x = 1</em>
<em>y = 1</em>
Step-by-step explanation:
<u>System of Equations</u>
We are given the system of equations:
2x + y = 3
x = 2y - 1
Substituting x in the first equation:
2(2y - 1) + y = 3
Operating:
4y - 2 + y = 3
5y = 3 + 2
y = 5/5 = 1
y = 1
Since:
x = 2y - 1
Then:
x = 2(1) - 1
x = 1
Solution:
x = 1
y = 1
ANSWER:
15 SLICES
Explanation:
Joe ate 2 slices (1/4 = 2/8), Rhoda ate 3 (3/8), Chris ate 4.
2+3+4= 9.
There are 3 pizzas divided into 8 slices per pizza.
3 x 8 = 24 ; 24 SLICES TOTAL
Subtract 9 (that’s what was consumed) from 24.
24-9 = 15 ; 15 SLICES LEFT OVER
pls mark brainliest hehe